Implementation of Ergonomics in Efforts to Increase Knowledge and Health of Smoked Fish Groups - Rapiah Sarfa Marasabessy; Yudhy Muchtar Latuconsina; Agung K Henaulu; Muhammad Alvuad Mualo; Rahul Lestaluhu; Besmin Jahawadan (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The process of curing fish in Pakarena Hamlet is done simply by using a smoking house with a shelf made of bamboo. The condition of the fumigation house, which is not ergonomic, causes the temperature of the work environment to be very hot and smoky. The smoking process, which lasts about 7 to 8 hours, makes the fish smokers sit for a long time. This condition causes many health problems, including shortness of breath, sore eyes, chest palpitations, and pain in the waist. In addition to health problems, other problems encountered in this business are their low knowledge and skills in managing the business, especially in the aspects of production, marketing, and financial management. The purpose of this community service is to improve the knowledge and health of the mothers of the fish smoking group related to the work environment and ergonomic work attitudes, financial and marketing management, as well as the manufacture of ergonomic smoking houses. The methods used are counseling and making an ergonomic smoking house. The results of the service show an increase in knowledge related to ergonomics and work attitudes as well as marketing strategies and financial management. The fumigation house that is made has a larger and higher capacity, is equipped with adequate air ventilation, and is made of permanent walls so that it can avoid the accumulation of hot smoke and reduce the environmental temperature so as to reduce complaints and shortness of breath.